N‐Heterocyclic Carbene–Phosphinidene Complexes of the Coinage Metals. Issue 45 (14th September 2015) - Doddi, Adinarayana; Bockfeld, Dirk; Nasr, Alexandre; Bannenberg, Thomas; Jones, Peter G.; Tamm, Matthias
Abstract Coinage metal complexes of the N‐heterocyclic carbene–phosphinidene adduct IPr⋅PPh (IPr=1, 3‐bis(2, 6‐diisopropylphenyl)imidazolin‐2‐ylidene) were prepared by its reaction with CuCl, AgCl, and [(Me2S)AuCl], which afforded the monometallic complexes [(IPr⋅PPh)MCl] (M=Cu, Ag, Au). The reaction with two equivalents of the metal halides gave bimetallic [(IPr⋅PPh)(MCl)2] (M=Cu, Au); the corresponding disilver complex could not be isolated. [(IPr⋅PPh)(CuOTf)2] was prepared by reaction with copper(I) trifluoromethanesulfonate. Treatment of [(IPr⋅PPh)(MCl)2] (M=Cu, Au) with Na(BArF) or AgSbF6 afforded the tetranuclear complexes [(IPr⋅PPh)2M4Cl2]X2 (X=BArF or SbF6), which contain unusual eight‐membered M4Cl2P2 rings with short cuprophilic or aurophilic contacts along the chlorine‐bridged M⋅⋅⋅M axes. Complete chloride abstraction from [(IPr⋅PPh)(AuCl)2] was achieved with two equivalents of AgSbF6 in the presence of tetrahydrothiophene (THT) to form [(IPr⋅PPh){Au(THT)}2][SbF6]2. The cationic tetra‐ and dinuclear complexes were used as catalysts for enyne cyclization and carbene transfer reactions.